2021
DOI: 10.3389/fped.2021.660076
|View full text |Cite
|
Sign up to set email alerts
|

Case Report and Review of the Literature: A New and a Recurrent Variant in the VARS2 Gene Are Associated With Isolated Lethal Hypertrophic Cardiomyopathy, Hyperlactatemia, and Pulmonary Hypertension in Early Infancy

Abstract: Mitochondriopathies represent a wide spectrum of miscellaneous disorders with multisystem involvement, which are caused by various genetic changes. The establishment of the diagnosis of mitochondriopathy is often challenging. Recently, several mutations of the VARS2 gene encoding the mitochondrial valyl-tRNA synthetase were associated with early onset encephalomyopathies or encephalocardiomyopathies with major clinical features such as hypotonia, developmental delay, brain MRI changes, epilepsy, hypertrophic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…CASP1 [185], FOXP3 [186], SOCS1 [187], GATA6 [188], IRF7 [189], POSTN (periostin) [190], CYP19A1 [191], CD36 [192], LYN (LYN proto-oncogene, Src family tyrosine kinase) [193], CD4 [194], LEPR (leptin receptor) [195], AR (androgen receptor) [196], FOXO1 [197] and PON2 [198] are a potential biomarkers for the detection and prognosis of PCOS. Udjus et al [199] Benjafield et al [200], Shetty et al [58], Kassan et al [201], Wetzl et al [202], Le Hiress et al [203], Pal-Ghosh et al [204], Niu, [205], Fan et al [206], Deng et al [207], Chen et al [208], Sardo et al [209], Seidel et al [210], Zhu et al [211], Omura et al [212], Hu et al [213], Castoldi et al [214], Yoshida et al [215], Palao et al [216], Kušíková et al [217], Decharatchakul et al [218], Ahmed et al [219], Merklinger et al [220], Lei et al [146], Liu et al [221], Chen et al [222], Tan et al [223], Shi et al [224], Ikonnikova et al [225], Shimodaira et al [226], Pravenec et al [227], Zhang et al [228], Shah et al [229], Cicekliyurt and Dermenci [230], Ong et al [98], Nowzari et al [163], Kim et al [231], Bonafiglia et al [232], Selle et al [233],Yoo et al [234], Kasacka et al [235], Wang et al [236], Huang et al [237], Caceres et al [238], Lei et al [239], Lu et al [240], Cui et al [241], Xiao et al [242], Hiramatsu et al [243], Oliver et al [244], Grabowski et al [245], Zhu et al [246] and Li et al [247] demonstrated that the altered expression of CASP1, EDNRA (endothelin receptor type A), F2RL1, FOXP3, TIMP4, CD74, PLK1, TGFB1, GATA6, IRF7, IRF9, BGN (biglycan), C...…”
Section: Discussionmentioning
confidence: 99%
“…CASP1 [185], FOXP3 [186], SOCS1 [187], GATA6 [188], IRF7 [189], POSTN (periostin) [190], CYP19A1 [191], CD36 [192], LYN (LYN proto-oncogene, Src family tyrosine kinase) [193], CD4 [194], LEPR (leptin receptor) [195], AR (androgen receptor) [196], FOXO1 [197] and PON2 [198] are a potential biomarkers for the detection and prognosis of PCOS. Udjus et al [199] Benjafield et al [200], Shetty et al [58], Kassan et al [201], Wetzl et al [202], Le Hiress et al [203], Pal-Ghosh et al [204], Niu, [205], Fan et al [206], Deng et al [207], Chen et al [208], Sardo et al [209], Seidel et al [210], Zhu et al [211], Omura et al [212], Hu et al [213], Castoldi et al [214], Yoshida et al [215], Palao et al [216], Kušíková et al [217], Decharatchakul et al [218], Ahmed et al [219], Merklinger et al [220], Lei et al [146], Liu et al [221], Chen et al [222], Tan et al [223], Shi et al [224], Ikonnikova et al [225], Shimodaira et al [226], Pravenec et al [227], Zhang et al [228], Shah et al [229], Cicekliyurt and Dermenci [230], Ong et al [98], Nowzari et al [163], Kim et al [231], Bonafiglia et al [232], Selle et al [233],Yoo et al [234], Kasacka et al [235], Wang et al [236], Huang et al [237], Caceres et al [238], Lei et al [239], Lu et al [240], Cui et al [241], Xiao et al [242], Hiramatsu et al [243], Oliver et al [244], Grabowski et al [245], Zhu et al [246] and Li et al [247] demonstrated that the altered expression of CASP1, EDNRA (endothelin receptor type A), F2RL1, FOXP3, TIMP4, CD74, PLK1, TGFB1, GATA6, IRF7, IRF9, BGN (biglycan), C...…”
Section: Discussionmentioning
confidence: 99%
“…Patients with mitochondrial dysfunction and oxidative phosphorylation deficiencies harboring VARS2 mutations were shown to have reduced amide acetylation of fibroblast tRNAs. 15 Variations in VARS2 have also been associated with combined oxidative phosphorylation deficiency 20, a mitochondrial respiratory chain complex disorder. 16 Mitochondria play a role in the generation not only of NETs but also of pro-inflammatory oxidized mitochondrial DNA in autoimmune diseases, 17 mitochondria and their components (e.g., N-formylated peptides and mtDNA) are recognized as damage-associated molecular patterns (DAMPs), which activate the innate immune system and elicit an inflammatory response, 18 ATP and reactive oxygen species (ROS), produced by mitochondria are triggers of the nuclear oligomerization domain (NOD)–like receptors and contribute to inflammasome activation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative phosphorylation (OXPHOS) was evaluated in fresh muscle and skin fibroblasts ( 14 ) ( Figure 2 ). Evaluation of OXPHOS in muscle (M. gastrocnemius right) revealed normal activities of the respiratory chain complexes I [24 mUnit/mg (18–59 mUnit/mg)], II [43 mUnit/mg, (28–69 mUnit/mg)], III [208 mUnit/mg, (149–480 mUnit/mg)], IV (cytochrome-C-oxidase) [214 mUnit/mg, (148–392 mUnit/mg)], V [92 mUnit/mg, (60–223 mUnit/mg)], and citrate synthase [122 mUnit/mg, (134–260 mUnit/mg)].…”
Section: Diagnostic Assessmentmentioning
confidence: 99%